2022
DOI: 10.3390/biomedicines10092066
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Empagliflozin Are Mediated by Reduced Renal Inflammation and Oxidative Stress in Spontaneously Hypertensive Rats Expressing Human C-Reactive Protein

Abstract: Gliflozins (inhibitors of sodium-glucose cotransporter 2) show many beneficial actions beyond their antidiabetic effects. The underlying mechanisms of these additional protective effects are still not well understood, especially under non-diabetic conditions. Therefore, we analyzed the effects of empagliflozin in young (3-month-old) and adult (12-month-old) male spontaneously hypertensive rats (SHR) expressing human C-reactive protein (CRP) in the liver. SHR-CRP rats are a non-diabetic model of metabolic syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Similar to our [ 21 , 22 , 23 ] and other investigations [ 13 , 19 ], we have found that relative kidney weight was increased in FHH and UNX-HS rats. Whether this increase is associated with the dilatation of tubular lumen due to SGLT-2-induced diuresis or due to tubular cell hypertrophy remains to be determined.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Similar to our [ 21 , 22 , 23 ] and other investigations [ 13 , 19 ], we have found that relative kidney weight was increased in FHH and UNX-HS rats. Whether this increase is associated with the dilatation of tubular lumen due to SGLT-2-induced diuresis or due to tubular cell hypertrophy remains to be determined.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, we did not demonstrate the improvement of cardiac function in hereditary hypertriglyceridemic rats, in which beneficial effects were mediated mainly through the improvement of hepatic lipid metabolism [ 21 ]. In contrast, in SHR-CRP rats, empagliflozin benefit was based on reduced renal inflammation and oxidative stress [ 23 ], which is in line with the findings of Ali et al [ 18 ], who also demonstrated a reduction in renal inflammation and ROS production in adenine-induced CKD. In addition, several studies ascribed renoprotection to the anti-fibrotic effects of gliflozins [ 17 , 19 , 28 ].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations